Performance evaluation of an RFID-based vehicle-miles-travelled revenue collection system. (10th April 2007) - Porter, J. David; Kim, David S.; Vergara, Hector A.; Long, Myra D.; , Daniel R. Staley
In 2001, Oregon State University (OSU) in collaboration with the Oregon Department of Transportation and the Road User Fee Task Force (RUFTF) began investigating a Vehicle Miles Travelled (VMT)-based alternative to the fuel tax. The culminating phase of this five year effort is the execution of a pilot test involving approximately 280 volunteer drivers. A specific VMT-based technology, referred to as the Pilot Test Technology Configuration (PTTC) will be used in the pilot test. This paper discusses the lessons learned in the design and development of the PTTC, especially the challenges faced with the use of RFID technology to identify and collect VMT data from equipped vehicles.